Dobutamine stress echocardiography for the detection of myocardial viability in patients with left ventricular dysfunction taking β blockers: accuracy and optimal dose. Issue 4 (1st April 2002) - Zaglavara, T; Haaverstad, R; Cumberledge, B; Irvine, T; Karvounis, H; Parharidis, G; Louridas, G; Kenny, A
Abstract : Objective: To assess the accuracy of dobutamine stress echocardiography (DSE) and the optimal dose of dobutamine to detect myocardial viability in patients with ischaemic left ventricular (LV) dysfunction who are taking β blockers, using the recovery of function six months artery revascularisation as the benchmark. Patients: 17 patients with ischaemic LV dysfunction (ejection fraction < 40%) and chronic treatment with β blockers scheduled to undergo surgical revascularisation. Setting: Regional cardiothoracic centre. Methods: All patients underwent DSE one week before and resting echocardiography six months after revascularisation. A wall motion score was assigned to each segment for each dobutamine infusion stage, using the standard 16 segment model of the left ventricle. The accuracy of DSE to predict recovery of resting segmental function was calculated for low dose (5 and 10 μg/kg/min) and for a full protocol of dobutamine infusion (5 to 40 μg/kg/min). Results: Of the 272 segments studied, 158 (58%) were dysfunctional at rest, of which 79 (50%) improved at DSE and 74 (47%) recovered resting function after revascularisation. Analysis of results with a low dose showed a significantly lower sensitivity and negative predictive value than with a full protocol (47% v 81%, p < 0.001 and 65% v 82%, p < 0.05, respectively). The accuracy in the full protocol analysis was comparable with that reported in patients no longer taking β blockers but was significantly lower than that in the low dose analysis (78% v 66%, p < 0.001). Conclusions: Findings suggest that β blocker withdrawal is not necessary before DSE when viability is the clinical information in question. However, a completed protocol with continuous image recording is required to detect the full extent of viability.